1975
DOI: 10.2134/agronj1975.00021962006700060024x
|View full text |Cite
|
Sign up to set email alerts
|

Potential Tetany Hazard of N‐Fertilized Bromegrass as Indicated by Chemical Composition1

Abstract: The objective of this field experiment was to determine the effect of N fertilization on yield and chemical composition of smooth bromegrass (Bromus inermis L.) and the potential for grass tetany hazard in the northern Great Plains as indicated by chemical composition of bromegrass forage. Chemical components of forage considered in relation to the hazard of tetany (a metabolic disorder of ruminants resulting from forage with low Mg availability) were inorganic cations, organic anions, aconitate, and % total N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The (NH 4 hS04 and urea were added alone or in combination with nitrapyrin at the rate of 1 mg for each 50 mg N. Treatments were replicated three times for a total of 48 pots which were weighed periodically and watered to 25% (W/W). The fertilizer and nitrapyrin (N-serve 3 ) were added in solution. Pots were filled with three increments of soil and water or fertilizer solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The (NH 4 hS04 and urea were added alone or in combination with nitrapyrin at the rate of 1 mg for each 50 mg N. Treatments were replicated three times for a total of 48 pots which were weighed periodically and watered to 25% (W/W). The fertilizer and nitrapyrin (N-serve 3 ) were added in solution. Pots were filled with three increments of soil and water or fertilizer solution.…”
Section: Methodsmentioning
confidence: 99%
“…The forage was oven dried at 65 C, ground, and analyzed for N, K, Ca, Mg, P, N0-3 -N, trans-aconitic acid, and ash alkalinity. Samples were digested with sulfuric acid and hydrogen peroxide in a block digestor (19) and analyzed for N and P by the Technicon 3 Auto Analyzer Industrial Method No. 334-74W/ B + revised March 1977.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of all these studies show that unless sampling conditions are closely standardised it will be difficult to identify clearly ,my significant seasonal patterns of variation. Nt/TWSC ratio Mayland et al (1974Mayland et al ( , 1975 and Follett et al (1975) studied chemical composition of crested wheatgrass (Agropyron desertorum) in relation to incidence of grass tetany in semi-arid ranges of the western U.S.A. Among the chemical indices nssociated with onset of tetany was a rapid increase in the ratio Nt/TWSC to values above 0.3.…”
Section: (B)mentioning
confidence: 99%
“…Recently, Lawrence (1980) The mineral composition of forage is important because of its relation to the occurence of grass tetany (Follett et al 1975 Mayland et al 1975). However, N fertilization can also have a large effect on the chemical composition of the forage (Barta et al 1973;Follett et al 1975;Mayland et al 1975). Kemp and 't Hart ( 1957) reported that a ratio of K/(Ca+Mg) greater than 2.2 in forage would likely result in grass tetany in animals fed on it.…”
mentioning
confidence: 99%